PENDIDIKAN JASMANI OUTDOOR BERBASIS JOYFUL LEARNING SEBAGAI STRATEGI PENINGKATAN KEMAMPUAN MOTORIK ANAK SEKOLAH DASAR - Gatot Jariono; Nurhidayat Nurhidayat; Eko Sudarmanto; Ardhian Tomy Kurniawan; Silva Regina Meilinawati; Haris Nugroho; Uzizatun Maslikah (STKIP Subang, 2026)
Motor competence plays a fundamental role in supporting the physical, cognitive, and social development of primary school children. However, physical education instruction is still predominantly characterized by conventional, teacher-centered approaches that limit students' active engagement and motor development. This community service program aimed to implement Outdoor Physical Education based on the Joyful Learning framework as a strategy to enhance students' motor competence. The program consisted of needs assessment, school coordination, instructional planning, guided implementation of outdoor game-based learning activities, and evaluation through observation, documentation, and pre- and post-program motor competence assessments. The activities were conducted collaboratively with physical education teachers and primary school students. The findings demonstrated improvements in students' motor competence, active participation, learning motivation, movement coordination, balance, and agility. In addition, teachers enhanced their ability to design innovative, contextual, and student-centered outdoor learning experiences. These results indicate that Joyful Learning-based Outdoor Physical Education is an effective strategy for improving both the quality of physical education instruction and the motor competence of primary school children. The program provides a practical and replicable model that can serve as a best practice for strengthening physical education in primary schools.